2018
DOI: 10.1080/14017431.2018.1459823
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in plasma L-arginine and methylarginines in heart failure and after heart transplantation

Abstract: Plasma L-Arginine concentrations normalize after HT. However, as ADMA is unchanged, the L-Arginine/ADMA-ratio remained low and correlated inversely to PVR. Together these findings suggest that (i) the L-Arginine/ADMA-ratio may be an indicator of pulmonary vascular tone after HT, and that (ii) NO-dependent endothelial function is partly restored after HT. Considering the good postoperative outcome, the biomarker levels may be considered "normal" after HT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Putrescine is an intermediate metabolite of the urea cycle. Fumarate is formed in the urea cycle, thus linking the urea cycle to the TCA cycle which involves the glucose aerobic oxidation and the major pathways of fat and amino acid metabolisms (Zou et al, 2015;Lundgren et al, 2018). Our results suggested that energy production during aerobic respiration was suppressed in rats with blood stasis.…”
Section: Discussionmentioning
confidence: 65%
“…Putrescine is an intermediate metabolite of the urea cycle. Fumarate is formed in the urea cycle, thus linking the urea cycle to the TCA cycle which involves the glucose aerobic oxidation and the major pathways of fat and amino acid metabolisms (Zou et al, 2015;Lundgren et al, 2018). Our results suggested that energy production during aerobic respiration was suppressed in rats with blood stasis.…”
Section: Discussionmentioning
confidence: 65%
“…Over recent years, it has been widely used in immunology and oncology [22,23]. Endothelial dysfunction is an important pathophysiological mechanism of developing HF and its decompensation, including disruption of the nitric oxide (NO) pathway [26]. The L-arginine-NO pathway is a complex system that affects vasomotor tone, cell adhesion, platelet aggregation, cell proliferation and angiogenesis [27].…”
Section: Problem Statement and Analysis Of The Latest Researchmentioning
confidence: 99%
“…73 Additionally, the use of the L-arginine to ADMA ratio for evaluating postoperative outcome in patients after heart transplant has been reported. 74 For Chagas disease, Carbajosa et al 75 demonstrated reduced plasmatic levels of L-arginine in mice during acute infection and increased survival rates when the mice were supplemented with 3.75 mg/kg of L-arginine in drinking water. 75 Based on this previous work, the role of the L-arginine to ADMA ratio as indicator of heart failure in Chagasic patients has been proposed.…”
Section: Markers Of Vascular Function In Chronic Chagasic Cardiomyopathymentioning
confidence: 99%